Acute Abdominal Pain Secondary to Chilaiditi Syndrome - David Kang; Andrew S. Pan; Michael A. Lopez; Jessica L. Buicko; Miguel Lopez-Viego (Case Reports in Surgery)
Chilaiditi syndrome is a rare condition occurring in 0.025% to 0.28% of the population. In these patients, the colon is displaced and caught between the liver and the right hemidiaphragm. Patients' symptoms can range from asymptomatic to acute intermittent bowel obstruction. Diagnosis is best achieved with CT imaging. Identification of Chilaiditi syndrome is clinically significant as it can lead to many significant complications such as volvulus, perforation, and bowel obstruction. If the patient is symptomatic, treatment is usually conservative. Surgery is rarely indicated with indications including ischemia and failure of resolution with conservative management.